Neomorphic leukemia-derived mutations in the TET2 enzyme induce genome instability via a substrate shift from 5-methylcytosine to thymine - Guang-Bo Jin; Shao-Qin Rong; Dong-Rui Yin; Zhou-Hao Deng; Xiao Ding; Meng-Yao Sheng; Hai Gao; Rahul M. Kohli; Guo-Liang Xu; Dan Zhou (Proceedings of the National Academy of Sciences, 2025)
Ten-eleven translocation (TET) enzymes oxidize 5-methylcytosine (mC) in DNA, contributing to the regulation of gene transcription. Diverse mutations of TET2 are frequently found in various blood cancers, yet the full scope of their functional consequences has been unexplored. Here, we report that a subset of TET2 mutations identified in leukemia patients alter the substrate specificity of TET2 from acting on mC to thymine. This neomorphic activity results from substitutions at key residues involved in the interactions with the mC base, including Asn1387 and His1904. Recombinant human TET2 proteins harboring the mutation of these residues can catalyze the oxidation of thymine to 5-hydroxymethyluracil (hmU) and 5-formyluracil (fU). Exogenous expression of the mutant TET2 Asn1387Thr (N1387T) in HEK293T cells leads to hmU accumulation, with levels further increased in cells lacking the glycosylase SMUG1. Endogenous knock-in of N1300T, the murine equivalent of N1387T, in mouse embryonic stem cells induces hmU production, causing DNA lesions and transcriptional activation of DNA damage response genes. N1300T cells accumulate more additional mutations with extended culture and exhibit heightened sensitivity to ATR inhibition compared to Tet2 knockout cells. Our study reveals that certain patient-derived TET2 mutations can acquire unexpected gain-of-function activities beyond impairing mC oxidation, offering a fresh perspective on the diverse molecular etiology of mutant TET2-related leukemogenesis.